Spesies Burung Famili Bucerotidae Pada Ekosistem Tahura Pocut Meurah Intan Sebagai Materi Pendukung Matakuliah Ekologi - Samsul Kamal; Mulyadi Mulyadi; Nurdin Amin; Rizky Ahadi (Biotik, 2019)
Pocut Meurah Intan Forest Park is a natural conservation area and a place of learning, however this condition has changed in line with the high activity of local residents such as illegal logging, forest conversion, wildlife hunting and forest burning. This study aims to determine the types of birds of the Bucerotidae family in the Pocut Meurah Intan Forest Park Ecosystem as a support material for Ecology courses. The method used in this study is the explorative survey method. As the result, this study found 4 (four) bird species from the family Bucerotidae, namely Buceros rhinoceros, Buceros bicornis, Anthrococeros albirostris and Aceros undulatus. The results of this study will be utilized and developed theoretically in Ecology courses in the form of reference books.